The Implementation Of Peer Assesment On Speaking For The Tenth Grade Students In SMA N 1 Wuryantoro In 2014/2015 Academic Year - Prihatini, Arista Nur; , Aryati Prasetyarini, M.Pd; , Dr. Anam Sutopo, M.Hum (2015)
The objectives of this research are to describe the implementation of peer assessment on speaking specifically the objective of the teaching, the materials used in teaching-learning process, and the procedures used in peer assessment on speaking, and describe the students' response toward the technique. The research was done to the tenth grade students of SMA N 1 Wuryantoro. As the sample, the researcher took 24 students of X-1 class. The data were collected from the observation in the classroom with the English teacher and interview with the six students of X-1 class of the tenth grade students of SMA N 1 Wuryantoro. After collecting the data and analyzing them, the researcher describes the research finding. Teaching using peer assessment technique was conducted in three meetings. It is appropriate in speaking teaching-learning of narrative text and helps the students to develop their speaking skill. The peer assessment technique gives positive impact to the success of teaching speaking with narrative text. Peer assessment technique helps the students to speak and give correction about their peer presentation on performance.Peer assessment helps students increase their speaking skill through pair work. The students are able to speak the words and sentences correctly. Studentss are more interested in joining teaching-learning activities, the students have development of speaking skill.